REKONSTRUKSI GENERIC TEACHING SKILL BERBASIS ERA BARU PADA MAHASISWA - Ni Ketut Erna Muliastrini dan Komang Pitriani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
Teaching practice students are asked to implement a learning plan in a device that has been prepared. The task of the lecturer is to monitor and guide the implementation of learning planning and the atability of mastering the teaching skills of students. Teaching skills are skills that are absolutely mastered by students as a prospective teacher. Teaching skills have an important function in supporting the success of the learning process.Students must master Generic Taching Skills including: 1. Skills in developing learning scenarios; 2. Skills to open and close learning; 3. Explaining skills; 4.Questioning skills; 5. Skills provide reinforcement; 6.Skills using media and tools; 7. Variety skills; 8.Skills guiding discussion; 9. Learning assessment skills; 10. Classroom management skills. Being a mandatory skill that students have as a candidate for regeneration educators must master Generic Taching Skills as a provision to create a superior quality of learners and quality.